The moderate substitution of Astragalus sinicus returning for chemical fertilizer improves the N cycle function of key ecological bacterial clusters in soil - Lv, Minghao; Wang, Yongdong; Chen, Xiaofen; Qin, Wenjing; Shi, Wencong; Song, Weifeng; Chen, Jingrui; Xu, Changxu (Frontiers in Microbiology, 2023)
Astragalus sinicus (Chinese milk vetch) is a well-established resource of organic fertilizer widely used in paddy soils to partially replace chemical fertilizers. However, the influence of returning Astragalus sinicus to fields on the soil bacterial communities remains poorly understood. Here, we used the different amounts of Astragalus sinicus partly replace chemical fertilizers and investigated the changes in soil physicochemical factors and the soil bacterial community structure responses. It was found that returning Astragalus sinicus to the field significantly increased total nitrogen (TN) and available phosphorus (AP) content in the soil (P < 0.05). We applied weighted gene correlation network analysis (WGCNA) to detect significant associations between the soil microbiome data and physicochemical factors. There are two key ecological clusters (MEturquoise and MEgreen) significantly correlated with soil nitrogen (N) levels, mainly containing Acidobacteria, Proteobacteria, and Chloroflexi. Astragalus sinicus partly replacing chemical fertilizers reduced the normalized stochasticity ratio (NST) of rare ASVs, abundance ASVs, MEturquoise, and MEgreen (P < 0.05), but did not affect the assembly process of all ASVs (P > 0.05). Our results further indicated that the moderate amount of Astragalus sinicus returned to the field effectively mitigated the trend of reduced N retention capacity of key ecological clusters caused by chemical fertilizer application. However, the large amount of Astragalus sinicus led to a significant increase in abundance in denitrification and a significant decrease in abundance in N fixation of the key ecological clusters. This implies that replacing chemical fertilizers with a moderate amount of Astragalus sinicus is more beneficial to key ecological clusters to maintain soil N levels, while a large amount of Astragalus sinicus returned to the field can accelerate soil N loss. From the perspective of the microbial community in paddy soil, this study provides new enlightenment and reference on how to find a good balance between the amount of Astragalus sinicus returned to the field and ecological environment security.